2022
DOI: 10.1111/apa.16296
|View full text |Cite
|
Sign up to set email alerts
|

Review highlights the importance of donor human milk being available for very low birth weight infants

Abstract: One of the key roles of neonatal units is to support the growth and development of preterm infants during the critical period between birth and term equivalent age. Nutritional care is an important part in this process, as it is crucial that these vulnerable babies receive sufficient nutrients. Human milk makes a major contribution to this goal. It also has an indirect effect on growth and development, by alleviating the risk of complications due to premature birth. 1 Mother's own milk is the first choice for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…According to their findings, different timings of enteral feeding introduction failed to effectively modify GI outcomes, whereas the use of exclusive breast milk during enteral feeding advancement significantly reduced the risk of FI and NEC. This is in line with the multiple protective effects of human milk and with the well-established negative role of formula feeding in NEC development, as extensively documented by longstanding evidence [ 37 , 38 , 39 , 40 , 41 ] and further confirmed by the present results. Hence, our findings highlight how the combination of increasing prematurity and placental vascular dysfunction with the following compromise of fetal hemodynamics significantly amplify the risk of adverse GI outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…According to their findings, different timings of enteral feeding introduction failed to effectively modify GI outcomes, whereas the use of exclusive breast milk during enteral feeding advancement significantly reduced the risk of FI and NEC. This is in line with the multiple protective effects of human milk and with the well-established negative role of formula feeding in NEC development, as extensively documented by longstanding evidence [ 37 , 38 , 39 , 40 , 41 ] and further confirmed by the present results. Hence, our findings highlight how the combination of increasing prematurity and placental vascular dysfunction with the following compromise of fetal hemodynamics significantly amplify the risk of adverse GI outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…DHM improves rates of MOM at discharge (Shenker et al, 2023) and reduces the consumption of formula milk, a well‐known risk factor for NEC in preterm infants (Picaud, 2022). The United States Food and Drug Administration states that systematic reviews of powdered infant formula report a relatively high contamination rate (2%–15%) of Cronobacter species (NACMCF, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…From February 2019, all the preterm infants less than 1500 g could be fed with human milk, which including mother’s own milk and DHM, even in the first few days, after we established our human milk bank. Many studies have shown that compared with formula milk, DHM can improve the feeding tolerance of infants, reduce the incidence of infection, NEC, BPD, and retinopathy of prematurity (ROP) [ 10 ] and reduce readmission and the risk of adolescent cardiovascular disease. Although pasteurization destroyed some components in DHM, the loss of nutrients was very small.…”
Section: Discussionmentioning
confidence: 99%